2020
DOI: 10.1111/eth.13033
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐related breakdowns in the coordination of mating in Enchenopa binotata treehoppers (Hemiptera: Membracidae)

Abstract: Temperature influences the expression of a wide range of behavioral traits in ectotherms, including many involved in the initiation of pair formation and mating. Although opportunities to mate are thought to be greatest when male and female activity overlap, sex‐specific behaviors and physiology could result in mismatched thermal optima for male and female courtship. Here, we investigate how conflicts in the thermal sensitivity of male and female courtship activity affect patterns of mating across temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 82 publications
0
40
0
Order By: Relevance
“…The mating rates in the treatment -control and controltreatment combinations were the highest at 38°C and 34°C, respectively, and the thermal sensitivity of the mating behavior of males was higher than that of females. Leith et al (2020) have also reported sexspeci c thermal sensitivity in the courtship activity of Enchenopa binotata. The authors reported that the males of this species exhibited a distinct peak of activity at moderate temperatures, while the females exhibited the greatest activity at the hot thermal extreme.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The mating rates in the treatment -control and controltreatment combinations were the highest at 38°C and 34°C, respectively, and the thermal sensitivity of the mating behavior of males was higher than that of females. Leith et al (2020) have also reported sexspeci c thermal sensitivity in the courtship activity of Enchenopa binotata. The authors reported that the males of this species exhibited a distinct peak of activity at moderate temperatures, while the females exhibited the greatest activity at the hot thermal extreme.…”
Section: Discussionmentioning
confidence: 89%
“…Such behavioral adaptation strategies for survival during adverse environmental stresses are also reported in other insects, such as hormesis and stimulated parasitic behavior induced in Encarsia formosa upon exposure to sublethal concentrations of spirotetramat (Yang et al, 2021), the increased courtship and heightened copulation behavior observed in Trichogramma chilonis exposed to an insecticide (Wang et al, 2020), etc. Temperature is also reported to in uence the expression of a wide range of behavioral traits in ectotherms, including several traits involved in the initiation of pair formation and mating (Leith et al, 2020). In the mating process of fruit ies, the male insects exhibit a series of courtship behaviors to attract females, while a high proportion of female insects refuse to mate (Shelly, 2001;Aquino and Joachim-Bravo, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral processes at all stages of mating change with temperature as a result (Leith et al, 2021). In the precopulatory stages, temperature affects the likelihood of individuals engaging in a precopulatory activity—an important prerequisite for mating in many animals—with the highest activity often occurring at intermediate temperatures (Brandt et al, 2018; Eberhard et al, 2019; Leith et al, 2020; Macchiano et al, 2019). Thus, the likelihood of mating to occur also often peaks at intermediate temperatures (Huey & Stevenson, 1979; Leith et al, 2020; Leith et al, 2021) with notable exceptions (Brandt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the precopulatory stages, temperature affects the likelihood of individuals engaging in a precopulatory activity—an important prerequisite for mating in many animals—with the highest activity often occurring at intermediate temperatures (Brandt et al, 2018; Eberhard et al, 2019; Leith et al, 2020; Macchiano et al, 2019). Thus, the likelihood of mating to occur also often peaks at intermediate temperatures (Huey & Stevenson, 1979; Leith et al, 2020; Leith et al, 2021) with notable exceptions (Brandt et al, 2018). Ambient temperature also affects copulation duration: copulation duration is often longest at colder temperatures (Brandt et al, 2018; Costa & Sotelo, 1984; Jiao et al, 2009; Katsuki & Miyatake, 2009; Leith et al, 2020; Michiels, 1992; Vasudeva et al, 2018; Yenisetti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%